Reconfigurable Modular System of Prefabricated Timber Grids. (May 2022) - Hua, Hao; Hovestadt, Ludger; Li, Biao
Abstract: To coordinate the old wisdom of modular systems and the emerging paradigm of Industry 4.0, the latest digital discretism has worked on combinatorial assembly for open-ended field conditions. Considering oriented to small-scale semipermanent timber buildings, this paper introduces a reconfigurable modular timber grid inspired by the traditional East Asian timber architecture. The system only requires minimum cuts on a dimensional timber to produce serialized components. As a result, the timber components dismantled from previous buildings can be easily reprocessed for other structures of different configurations. This recycling scheme facilitates serial manufacturing and reduces resource consumptions. Such a reconfigurable system relies on the grid geometry and the local topology of connections. The formalism of Bravais lattice from crystallography facilitates the analysis of the symmetry in various regular grids. Our prototype of the timber grid is self-standing (without connections to the ground) and creates a large overhang. A finite element method is developed to evaluate the structural performance of timber structures with semirigid joints on the basis of the direct stiffness method. Traditional East Asian architecture uses the interlocking mechanism for wood connections, whereas our system uses shallow-notched joints on the wood. A robotic milling system is adopted to prefabricate the wood components. The shallow notches are modeled as Boolean operations between a pair of cuboid components, which greatly simplifies the toolpath planning of the robotic system. System design, serial production of components, assembly, and recycling are integrated within a consistent and open system. Highlights: The reconfigurable timber grid optimizes material supply and energy consumption. Bravais lattice from crystallography reveals the symmetry in regular timber grids. Timber components from previous buildings can be easily reprocessed for reuse. Finite element method models the semirigid connections in timber grid. Robotic milling system is adopted to prefabricate the wood components.